Feasibility Study of Cold Formed Steel Profile on Roof of Type 36 Housing Bumi Findari Mas 2 Maros Regency - Katsir, Muhammad Hamdan; Listyawan, Anto Budi (Universitas Muhammadiyah Surakarta, 2023)
Cold formed steel construction is one of the materials that is often used in a roof truss onstruction, considering the use of cold formed steel is relatively fast and practical. Bumi Findaria Mas 2 Residence is one of the housing estates that provides subsidized housing for Low-Income Communities, whose roof structure uses lightsteel. With the development of technology at this time there are many applications that make it easier for technicians to analyze a building construction, one application that is often used to analyze structures is SAP2000. In this analysis, the author will try a feasibility study on the roof truss structure of a subsidized house type 36 in the Bumi Findaria Mas 2 under The Directorate General of Housing Maros Regency in the Internship-MBKM program run by the Minister of Education and Culture. The profile used for the roof truss for the Bumi Findaria Mas 2 housing is cold formed steel C75x35x0.65. In the roof truss analysis the authors calculate the roof truss by looking at the Interaction Ratios results from the SAP2000 analysis. The results of the analysis using C75x35x0.65 cold formed steel profiles show a Interaction Ratios of more than one, meaning that the profile is not suitable for use. After knowing the results of the analysis, the authors tried to use the C75x35x1 profile, and the results obtained by the Interaction Ratios were below one, indicating that the steel profile was feasible to use.